Analisis Soal Ujian Nasional Ilmu Pengetahuan Alam Sekolah Menengah Pertama Tahun Ajaran 2016/2017 - Lambok Verayanty Siregar; Rini Rita T. Marpaung; Berti Yolida (Universitas Lampung, 2018)
The aim of this research is to reveal the characteristics of the items of Science subject in national examination for Junior High School in the 2016/2017 academic year.This research is qualitative using documentation study. The subjects of this research is the questions of national examination. Data collection techniques through documentation study by analy-zing national examinations questions and Focus Group Discussion (FGD). The design of this research is descriptive. The data in this study were also analyzed by using qualitative descriptive. The results of the study show that the national examination questions with the most stimulus are in the form of medium categories (52,5%). Furthermore, the most important indicator of critical thinking ability is determining the conclusions which is in the least category (22,5%). Moreover, the indicator of the most problem solving skills is identifying problems which is belong to the least category (22,5%). In addition, the national examination has the suitability of the items with the high achievement competency indicators (98%).Penelitian ini bertujuan untuk mengungkapkan karateristik butir soal mata pelajaran IPA pada ujian nasional tingkat SMP tahun ajaran 2016/2017. Penelitian ini merupakan penelitian kualitatif menggunakan studi dokumentasi. Subjek penelitian yaitu, soal ujian nasional. Instrumen peneli-tian menggunakan lembar penilaian dan rubrik penilaian. Teknik pengumpulan data melalui studi dokumentasi dengan menganalisis soal Nasional dan Focus Group Discussion (FGD). Data pada penelitian ini juga dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan soal ujian nasional dengan stimulus paling banyak adalah dalam bentuk gambar yang berkategori sedang (52,5%). Indikator kemampuan berpikir kritis paling banyak adalah menentukan kesimpulan yang berkategori sedikit (22,5%). Indikator keterampilan pemecahan paling banyak adalah mengidentifikasi masalah yang berkategori sedikit (22,5%). Ujian nasional memiliki kesesuaian butir soal dengan indikator pencapaian kompetensi yang berkategori tinggi sekali (98%).Kata kunci: analisis soal, kesesuaian, ujian nasional